The impact of foreign direct investment on economic growth in Malaysia / Masturah Ma'in and Siti Sarah Mat Isa - Ma'in, Masturah; Mat Isa, Siti Sarah (Universiti Teknologi Mara Selangor, 2020)
This study analyzes the impact of Foreign Direct Investment (FDI) on economic growth in Malaysia. The Auto-Regressive Distributed Lag (ARDL) method is used to investigate the long-run relationship between FDI and economic growth. The controlled variables are life expectancy, gross fixed capital formation and population growth. The bound test suggests that FDI, life expectancy, gross fixed capital formation and population growth have a long-run relationship with economic growth. This is supported by the significant correction term, which confirms the existence of a long-run relationship. However, as FDI, life expectancy and gross fixed capital formation have positive impact on Malaysia's economic growth, population on the other hand, shows otherwise.